Case report: Generalized granuloma annulare successfully treated with baricitinib in two cases - Marina Yunoki; Shumpei Kondo; Masaki Otsuka; Yoshiki Tokura; Yoshiki Tokura (Journal of Cutaneous Immunology and Allergy)
Treatments are challenging in generalized granuloma annulare. We reported two cases of generalized granuloma annulare without diabetes mellitus; one exhibited non-annular papules and the other did patch/annular lesions. Since they were refractory to multiple treatments, we treated them with JAK inhibitor baricitinib at 2 mg daily. After 1–2-month treatment, they responded well to baricitinib with good tolerance. Given increased JAK1 signaling, high interferon-α and -γ production and macrophage activation in granuloma annulare, JAK inhibitors are considered to be a reasonable choice for recalcitrant generalized granuloma annulare. In addition to the reported cases, our two cases further support the effectiveness of JAK inhibitors for generalized granuloma annulare.